Handling of Election Violations in the Election of Regency/City DPRD Members at the Election Supervisory Agency (Bawaslu) of Konawe Regency - Hasjad Hasjad (Jurnal Restorasi : Hukum dan Politik, 2024)
The handling of election violations in the election of members of the Regency/City DPRD at the Bawaslu of Konawe Regency is carried out in several stages. First, election supervisors submit recommendations and files of the results of the study of alleged administrative violations to the General Elections Commission (KPU), Provincial KPU, Regency/City KPU, PPK, or PPS according to the level. For criminal election violations, the violation report files and the results of the study are forwarded by the election supervisors to the Indonesian National Police (POLRI) investigators no later than x 24 hours after the decision by the election supervisors. In addition, the Bawaslu of Konawe Regency also handles election process disputes carried out by the parties. If the resolution of the election process dispute carried out by Bawaslu is not accepted by the parties, the parties can file legal action with the state administrative court. The entire Bawaslu decision-making process must be carried out through an open and accountable process. The results of the study found that the handling of election crimes is based on empirical facts in Konawe Regency. Data collected regarding the handling of election criminal cases in the three cities has several similarities and differences. In handling election violations, the Bawaslu of Konawe Regency also considers provisions regarding the procedures for handling election crimes, which consist of three parts. The first section regulates the procedures for handling election crimes, and the second section regulates the Special Election Crimes Council. In summary, the handling of election violations in the election of members of the Regency/City DPRD at the Konawe Regency Election Supervisory Agency (Bawaslu) is carried out in several stages, including administrative supervision, handling of criminal violations, and handling of election process disputes